2021
DOI: 10.1186/s13020-020-00417-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of intestinal flora: accompany with the antihypertensive effect of electroacupuncture on stage 1 hypertension

Abstract: Background Increasing evidence have indicated the relationship between intestinal dysbiosis and hypertension. We aimed to evaluate the effect of the electroacupuncture (EA) on intestinal microbiota in patients with stage 1 hypertension. Methods 93 hypertensive patients and 15 healthy subjects were enrolled in this study. Applying a highly accurate oscillometric device to evaluate the antihypertensive effect of EA. 16S rRNA sequencing was used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 73 publications
1
44
1
Order By: Relevance
“…Table 4). Of these assessments, seven (7/13) [14, 30, 34, 36, 37, 40, 41] provided data and were included in meta-analyses. We used bacterial diversity indexes (Shannon and Simpson indexes, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4). Of these assessments, seven (7/13) [14, 30, 34, 36, 37, 40, 41] provided data and were included in meta-analyses. We used bacterial diversity indexes (Shannon and Simpson indexes, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten (10/16) studies [14, 24, 30, 33, 34, 37, 39-41] measured the β-diversity of gut microbiota mainly using principal coordinate analysis or principal component analysis. Consistent differences between hypertensive and control were reported by eight (8/10) studies [14, 24, 30, 33, 34, 36, 40, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Our results provide important information on how resveratrol alters gut microbes and restores the balance of TH17/Treg to prevent the programming of hypertension. Additionally, low level of genus Lachnoclostridium but high abundance of Ruminiclostridium has been identified in hypertensive patients [ 35 , 36 ]. According to our data, resveratrol treatment increased Lachnoclostridium and decreased Ruminiclostridium_9 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the data in this work showed that resveratrol protects against adenine-induced hypertension and kidney damage, which coincides with an abundance of the genera Parabacteroides , Blautia , and Alistipes. Given that the abundance of the genera Alistipes and Blautia was inversely associated with BP [ 29 , 30 ], that resveratrol increased the abundance of the genera Parabacteroides , and Alistipes was associated with protection against kidney damage in a diabetic nephropathy model [ 31 ], it is possible that resveratrol can influence these microbes towards renoprotection and have a BP-lowering benefit.…”
Section: Discussionmentioning
confidence: 99%